The Functional Crisis of Madrasah: Between State Standardization and the Instrumentalization of Religious Identity in Indonesia - Chodijah Asy Syarifah; Evi Nurdiana; Robin; Muchammad Aqib Junaidi (Kartika: Jurnal Studi Keislaman, 2026)
Madrasahs, as Islamic social institutions in Indonesia, face increasingly complex challenges due to the influence of state education policies and the dynamics of religious identity. This study aims to analyze changes in the functions of madrasahs through three main aspects: shifts in religious traditions resulting from educational standardization; disruptions to institutional functions caused by the exploitation of religious identity for purposes other than education; and the ability of madrasahs to maintain their roles and identities. The study employs a qualitative approach using a literature review analyzed through qualitative content analysis and interpretive analysis, drawing on the perspectives of Pierre Bourdieu, Talcott Parsons, and the theory of institutional resilience. The research findings indicate that, first, educational standardization policies have driven a shift in the orientation of madrasahs from a pesantren-based scholarly tradition toward meeting academic and administrative standards; second, the use of religious identity for purposes beyond educational functions has the potential to weaken the role of madrasahs in preserving shared values and social integration; third, pesantren-based madrasahs demonstrate adaptability through the strengthening of scholarly traditions, curriculum integration, and the leadership of kiai who are responsive to change. This study confirms that the function of madrasahs continues to undergo adjustments in the interplay between state policy, socio-religious dynamics, and the evolving traditions of Islamic education within society.